2018
DOI: 10.1016/j.anbehav.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

In wolves, play behaviour reflects the partners' affiliative and dominance relationship

Abstract: Puppy packs (consisting of only puppies) and mixed-age packs (composed of puppies and adults) were observed to test whether social play can be used for assessing and establishing social relations in wolves, Canis lupus. Differently from previous studies, we looked at play behaviours in detail, allowing us to categorize play interactions as either competitive or relaxed, and predicted that different types of play would be associated with different relationships between individuals. We found that the more time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The large communicative repertoire of meerkats seems to provide the basis for their behavioural synchronization and cooperation during group activities (Gall et al 2017). We hypothesize that, as it occurs in other highly cohesive species (wolves, Cordoni 2009, Cafazzo et al 2018dogs, Palagi et al 2015, Byosiere et al 2016spotted hyena, Drea et al 1996;Tonkean macacques, Scopa and Palagi 2016;bonobos, Palagi 2008), in meerkats the capacity to manage play fighting can be achieved by the use of specific communicative signals of both auditory and visual nature.…”
Section: Introductionmentioning
confidence: 92%
“…The large communicative repertoire of meerkats seems to provide the basis for their behavioural synchronization and cooperation during group activities (Gall et al 2017). We hypothesize that, as it occurs in other highly cohesive species (wolves, Cordoni 2009, Cafazzo et al 2018dogs, Palagi et al 2015, Byosiere et al 2016spotted hyena, Drea et al 1996;Tonkean macacques, Scopa and Palagi 2016;bonobos, Palagi 2008), in meerkats the capacity to manage play fighting can be achieved by the use of specific communicative signals of both auditory and visual nature.…”
Section: Introductionmentioning
confidence: 92%
“…Peaceful cohesiveness is a feature of wolf society that is guaranteed also by playful activity [54,60,78]. Although most studies have focused on play in domestic dogs [6,79,80,81], this behavior does not appear as an artefact of domestication since also wolves play even during adulthood [78,82].…”
Section: The Playful Wolf: Tactics and Plasticity For A Deeper Knomentioning
confidence: 99%
“…It has been suggested that, through play, adult subjects can evaluate and manipulate the social relationships with group-members [71]. Cafazzo and colleagues [82] investigated play behavior in four captive wolf packs, two composed by immature peers and the other two by mixed-age subjects (puppies and adults). A positive linkage between play frequency and relationship quality was found; indeed, those dyads that spent more time in relaxed play (defined as play sessions involving a limited number of offensive patterns) engaged in more interactions belonging to the affinitive domain.…”
Section: The Playful Wolf: Tactics and Plasticity For A Deeper Knomentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is uncommon that animal play behaviour extends to adulthood, although some examples also exist for play behaviour occurring among individuals of mixed age-classes (e.g. [5,6]). Also, although examples exist (e.g.…”
Section: Introductionmentioning
confidence: 99%